Explaining tourists´ support for environmental protection - Campos-Soria, Juan Antonio; García-Pozo, Alejandro; Sánchez-Ollero, José Luis (My University, 2016)
Any movement towards sustainable tourism is dependent not only upon the industry and other key stakeholders but also the demand side, namely the tourists. Yet, there is a limited literature from the demand point of view. In this area, contributions to an understanding of tourists’ support to sustainable development are necessary. This paper analyzes the main determinants in tourist behavior regarding the environmental considerations when they are making decisions about their holiday plans. General literature on this issue highlights the need to consider socio-economic variables of the individual as well as the attributes related of their style of living. If the econometric model takes into account all these variables simultaneously, then the linkage between contextual changes and tourists´ behaviour is enriched and it may be estimated more accurately. In this sense, a multilevel approach using a random-intercept logistic models is proposed, since tourists belong to a country are affected by the same contextual variables. The analysis comprises a joint dataset composed by microdata belong to the survey Attitudes of Europeans Towards Tourism, which corresponds to Flash Eurobarometer 281, macrodata from Eurostat (GDP in pps and GDP growth) and additional variables profiles from the 2005 Environmental Sustainability Index. Country-specific effects are calculated across the EU-27 countries, which corroborated that attitudes to the sustainable tourism are heterogeneous geo-graphically. The higher the level of GDP, the lower the level of tourists´ support. These results could be explained because tourists of richer countries already have to pay more tax for envi-ronmental protection. Age, gender and educational attainment are relevant. Motivations for travelling, size of the community, type of the destination, and environmental sustainability indi-cators of the place of residence are also important factors.
Keywords: Turismo - Aspectos ambientales - Tesis doctorales; Tourism attitudes; Environment; Multilevel analysis